Fluid structure interaction of renal arteries of abdominal aorta subjected to single and double stenosed complication - Basri, Adi Azriff; S. M., Abdul Khader; Johny, Cherian; Pai, Raghuvir; Zuber, Mohammed; Ahmad, Zainuldin; Ahmad, Kamarul Arifin (Universiti Putra Malaysia Press, 2020)
Introduction: In this study, Renal artery (RA) stenosis of Single Stenosed (SS) and Double Stenosed (DS) with the condition of Normal Blood Pressure (NBP) and High Blood Pressure (HBP) were investigated using the aid of Fluid Structure Interaction (FSI) approach. Methods: Numerical analysis of 3D model patient’s specific abdominal aorta with RA stenosis was conducted using FSI solver in software ANSYS 18. Results: The results of velocity profile, pressure drop, time average wall shear stress (TAWSS), Oscillatory shear index (OSI) and total deformation of SS and DS with the condition of NBP and HBP were compared in terms of blood flow and structural wall tissue behaviour. The results concluded SS-NBP produced the highest value of velocity profile, TAWSS and OSI parameter compared to the others. Meanwhile, SS-HBP indicates the highest value pressure drop. On the other hand, SS-HBP and DS-HBP have a higher distribution of deformation contour and also maximum VMS compared to SS-NBP and DS-HBP. Conclusion: With the aid of FSI approach, this studied has proven that the existence of SS at RA location has a higher impact on the velocity magnitude, higher pressure drop, higher TAWSS and OSI value compared to the DS case. This is due to a high concentration of pressure acting at the narrow blood vessel of SS compared to DS cases which most of the blood flow will pass to the lower part of abdominal aorta.